Potential Alternative Therapeutic Modalities for Management Head and Neck Squamous Cell Carcinoma: A Review - Keihan Afshari; Karpal Singh Sohal (Cancer Control, 2023)
Head and neck squamous cell carcinoma (HNSCC) includes malignancies of the lip and oral cavity, oropharynx, nasopharynx, larynx, and hypopharynx. It is among the most common malignancy worldwide, affecting nearly 1 million people annually. The traditional treatment options for HNSCC include surgery, radiotherapy, and conventional chemotherapy. However, these treatment options have their specific sequelae, which produce high rates of recurrence and severe treatment-related disabilities. Recent technological advancements have led to tremendous progress in understanding tumor biology, and hence the emergence of several alternative therapeutic modalities for managing cancers (including HNSCC). These treatment options are stem cell targeted therapy, gene therapy, and immunotherapy. Therefore, this review article aims to provide an overview of these alternative treatments of HNSCC.